PARATHYROID ADENOMA WITH MISLEADING PHOSPHATE EXCRETION TESTS. Issue 6 (November 1960) - Morgan, H. G.; Stewart, W. K.; Grieve, J.
Abstract : A patient with primary hyperparathyroidism is described in whom, pre-operatively, the renal tubular handling of phosphate was within the limits accepted by recent writers as normal. The tests they advocate were, therefore, shown to be unreliable in this disease. The hypercalcaemia of primary hyperparathyroidism is one type of hypercalcaemia that is apparently not reduced to normal after the administration of an adequate dosage of cortisone. In our patient, such a "cortisone-fast" finding is documented, and was a valuable aid in the decision to operate.